The Role of Zakat Management Units in Enhancing Productive Zakat Governance - Karina Zulaikha (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the management of zakat by the Zakat Collection Unit (UPZ) of the Ministry of Religious Affairs in Jepara, focusing on the dual distribution model—consumptive and productive—and its implications for the empowerment of mustahik. Research Design & Methods: The research uses a qualitative field approach through interviews with mustahik, observation of zakat programs, and analysis of relevant regulations. The data is validated with the latest international literature on zakat governance, Islamic social finance, and poverty alleviation to provide a comprehensive picture. Findings: The results show that consumptive zakat is effective in meeting immediate needs, but its long-term impact is limited. Conversely, productive zakat through revolving livestock and business capital schemes can improve the socio-economic resilience of mustahik when accompanied by training and mentoring. The shift from revolving livestock to business capital demonstrates institutional adaptability in the face of technical constraints and external shocks, such as the COVID-19 pandemic. Hybrid governance—centralized supervision by BAZNAS with local innovation by UPZ—is able to strengthen accountability and contextual relevance. Implications & Recommendations: This study emphasizes the importance of integrating zakat into the Islamic social finance framework, with sustainability supported by capacity building, formal agreements, and continuous monitoring. Policymakers are encouraged to promote hybrid governance, diversify productive zakat models, and strengthen partnerships with microfinance institutions (BMT) to maximize the impact of empowerment. Contribution & Value Added: This study enriches the literature on zakat by providing empirical evidence on how institutional adaptation and hybrid governance can strengthen the transformative role of zakat. These findings show that productive zakat is not a uniform model, but must be adapted to local socio-economic realities, thus serving as a lesson for Muslim-majority countries that are institutionalizing zakat.